Cbl proteins in platelet activation. (September 2013) - Buitrago, Lorena; Tsygankov, Alexander; Sanjay, Archana; Kunapuli, Satya P.
<x xml:space="preserve">Abstract</x> Platelets play a fundamental role in hemostasis. Their functional responses have to be tightly controlled as any disturbance may lead to bleeding disorders or thrombosis. It is thus important to clearly identify and understand the signaling mechanisms involved in platelet function. An important role of c-Cbl and Cbl-b ubiquitin ligases in platelet functional responses and in hematological malignancies has been recently described. Cbl proteins perform negative and positive regulation of several signaling pathways in platelets. In this review, we explore the role of Cbl proteins in platelet functional responses.